New nitrosyl ruthenium complexes with combined activities for multiple cardiovascular disorders. Issue 16 (27th March 2023) - Gouveia Júnior, Florêncio Sousa; Silveira, João Alison de Moraes; Holanda, Thais Muratori; Marinho, Aline Diogo; Ridnour, Lisa A.; Wink, David A.; de Siqueira, Rodrigo José Bezerra; Monteiro, Helena Serra Azul; Sousa, Eduardo Henrique Silva de; Lopes, Luiz Gonzaga de França
Abstract : New ruthenium nitrosyl complexes were synthesized and characterized by spectroscopic techniques, including X-ray absorption. Under selected conditions, they were able to release NO and HNO, which was demonstrated through in vitro cell assays. Abstract : Nitrosyl ruthenium complexes are promising platforms for nitric oxide (NO) and nitroxyl (HNO) release, which exert their therapeutic application. In this context, we developed two polypyridinic compounds with the general formula cis -[Ru(NO)(bpy)2 (L)] n +, where L is an imidazole derivative. These species were characterized by spectroscopic and electrochemical techniques, including XANES/EXAFS experiments, and further supported by DFT calculations. Interestingly, assays using selective probes evidenced that both complexes can release HNO on reaction with thiols. This finding was biologically validated by HIF-1α detection. The latter protein is related to angiogenesis and inflammation processes under hypoxic conditions, which is selectively destabilized by nitroxyl. These metal complexes also presented vasodilating properties using isolated rat aorta rings and demonstrated antioxidant properties in free radical scavenging experiments. Based on these results, the new nitrosyl ruthenium compounds showed promising characteristics as potential therapeutic agents for the treatment of cardiovascular conditions such as atherosclerosis, deserving further investigation.